2006
DOI: 10.1110/ps.062139406
|View full text |Cite
|
Sign up to set email alerts
|

2005 Emil Thomas Kaiser Award

Abstract: Collagen is the most abundant protein in animals. The conformational stability of the collagen triple helix is enhanced by the hydroxyl group of its prevalent (2S,4R)-4-hydroxyproline residues. For 25 years, the prevailing paradigm had been that this enhanced stability is due to hydrogen bonds mediated by bridging water molecules. We tested this hypothesis with synthetic collagen triple helices containing 4-fluoroproline residues. The results have unveiled a wealth of stereoelectronic effects that contribute m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
39
0

Year Published

2007
2007
2009
2009

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 34 publications
(39 citation statements)
references
References 51 publications
0
39
0
Order By: Relevance
“…A crystal structure of the pyrrolidine ring of 16 showed that the methyl group in the 2-position stabilizes the exo conformation of the thiazolidine ring. This conformation is actually less stable than the endo conformation in the unsubstituted Pro residues found in proteins (28). Supporting the possibility that this difference may be important for activity, quantum mechanical calculations also identified exo as the minimum-energy conformation, shown overlaid with the crystal structure in Fig.…”
Section: Determining Of the Ring Geometry Of The Pro Analog In Integrmentioning
confidence: 83%
See 1 more Smart Citation
“…A crystal structure of the pyrrolidine ring of 16 showed that the methyl group in the 2-position stabilizes the exo conformation of the thiazolidine ring. This conformation is actually less stable than the endo conformation in the unsubstituted Pro residues found in proteins (28). Supporting the possibility that this difference may be important for activity, quantum mechanical calculations also identified exo as the minimum-energy conformation, shown overlaid with the crystal structure in Fig.…”
Section: Determining Of the Ring Geometry Of The Pro Analog In Integrmentioning
confidence: 83%
“…Substituents in Pro analogs have an important effect on their conformational properties, which in turn strongly affect the energetics of ligand interactions with their receptors (28,29). Thus, we examined the preferred conformations of the Pro analog in the potent compounds 15 and 16 in contrast to the less potent compound 22, which combined the substitutions in 15 and 16.…”
Section: Determining Of the Ring Geometry Of The Pro Analog In Integrmentioning
confidence: 99%
“…The stabilizing effect of 4(R)-hydroxylation of proline residues in the Yaa position of the collagen repeated -Gly-Xaa-Yaa-sequence can be explained by the stereoelectronic effects on the cis/trans ratio of Pro bonds, the strength of the hydrogen bond between Gly-NH and Xaa-CO, and the puckering of pyrrolidine ring. 20 The partial specific volume of (Gly-Pro-4(R)Hyp) 9 increases upon triple helix formation, indicating an increase in water binding upon structure formation. 21 However, the partial specific volume of (Gly-4(R)Hyp-(4(R)Hyp) 9 The structure of the collagen triple helix is completely different from that of globular proteins.…”
Section: Introductionmentioning
confidence: 99%
“…We did so by installing functional groups at C γ that mediate such effects, as well as reciprocal steric effects ( Figure 1). 30,31 For example, replacing Hyp with (2S,4R)-4-fluoroproline (Flp), which has the native-like stereochemistry, but not (2S,4S)-4-fluoroproline (flp) results in triple helices with markedly enhanced stability (Table I). [32][33][34] This and other results revealed that a gauche effect in Hyp and Flp mandates a C γ -exo pucker in the pyrrolidine ring, 34,35 which preorganizes the φ, ψ, and ω dihedral angles to those required for triple-helix assembly.…”
Section: Introductionmentioning
confidence: 99%
“…30,31 Beneficial preorganization prescribes that triple helices should be stabilized by proline derivatives in the Xaa position that prefer the C γ -endo pucker and by proline derivatives in the Yaa position that prefer the C γ -exo pucker. We reasoned that 4-chloro substitution, as in (2S,4S)-4-chloroproline (clp) and (2S,4R)-4-chloroproline (Clp), could control proline ring pucker and modulate collagen stability in much the same manner as does a 4-fluoro substitution (Figure 1).…”
Section: Introductionmentioning
confidence: 99%